Neutrophil-lymphocyte ratios in the prognostication of primary non-metastatic nasopharyngeal carcinoma - Liew,Kong Yew (2018)
Abstract Introduction: Nasopharyngeal carcinoma is a geographically and racially variable disease which has a high incidence in Malaysia. Based on current concepts in tumour related inflammation the inflammatory marker, neutrophil-lymphocyte ratio was tested to find its relationship with prognosis in nasopharyngeal carcinoma. Objective: To investigate the effect of the neutrophil-lymphocyte ratio on prognosis in non-metastatic primary nasopharyngeal carcinoma patients and to further refine the cut off between high and low neutrophil-lymphocyte ratio values. Methods: The medical charts of patients with histologically confirmed nasopharyngeal carcinoma from 1st January 2005 until 31st December 2009 were reviewed retrospectively and theneutrophil-lymphocyte ratio was calculated to see if there was any association between their higher values with higher failure rates. Results: Records of 98 patients (n = 98) were retrieved and reviewed. Only neutrophil-lymphocyte ratio (p = 0.004) and tumor node metastasis staging (p = 0.002) were significantly different between recurrent and non-recurrent groups, with the neutrophil-lymphocyte ratio being independent of tumor node metastasis staging (p = 0.007). Treatment failure was significantly higher in the high neutrophil-lymphocyte ratio group (p = 0.001). Disease free survival was also significantly higher in this group (p = 0.000077). Conclusion: High neutrophil-lymphocyte ratio values are associated with higher rates of recurrence and worse disease free survival in non-metastatic nasopharyngeal carcinoma patients undergoing primary curative treatment.